Genomic adaptation of the Lactobacillus casei group. - Hidehiro Toh (Public Library of Science (PLoS), 2013)
Lactobacillus casei, L. paracasei, and L. rhamnosus form a closely related taxonomic group (Lactobacillus casei group) within the facultatively heterofermentative lactobacilli. Here, we report the complete genome sequences of L. paracasei JCM 8130 and L. casei ATCC 393, and the draft genome sequence of L. paracasei COM0101, all of which were isolated from daily products. Furthermore, we re-annotated the genome of L. rhamnosus ATCC 53103 (also known as L. rhamnosus GG), which we have previously reported. We confirmed that ATCC 393 is distinct from other strains previously described as L. paracasei. The core genome of 10 completely sequenced strains of the L. casei group comprised 1,682 protein-coding genes. Although extensive genome-wide synteny was found among the L. casei group, the genomes of ATCC 53103, JCM 8130, and ATCC 393 contained genomic islands compared with L. paracasei ATCC 334. Several genomic islands, including carbohydrate utilization gene clusters, were found at the same loci in the chromosomes of the L. casei group. The spaCBA pilus gene cluster, which was first identified in GG, was also found in other strains of the L. casei group, but several L. paracasei strains including COM0101 contained truncated spaC gene. ATCC 53103 encoded a higher number of proteins involved in carbohydrate utilization compared with intestinal lactobacilli, and extracellular adhesion proteins, several of which are absent in other strains of the L. casei group. In addition to previously fully sequenced L. rhamnosus and L. paracasei strains, the complete genome sequences of L. casei will provide valuable insights into the evolution of the L. casei group.